2008
DOI: 10.1002/jssc.200700310
|View full text |Cite
|
Sign up to set email alerts
|

Studies of polyamines transport through liquid membranes with D2EHPA as a carrier

Abstract: The transport of polyamines through the liquid membranes with di-2-ethylhexyl phosphoric acid (D2EHPA) was investigated. The study was performed in three main steps: liquid-liquid extraction (LLE), bulk liquid membrane (BLM) extraction, and supported liquid membrane (SLM) extraction. Equilibrium distribution experiments allowed determining the extraction constants and stoichiometric coefficients for each polyamine. It turned out that one amino group binds two molecules of carrier (one D2EHPA dimer) and the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The detailed general theory of the SLM extraction process with a stagnant acceptor has been thoroughly described by Jönsson et al [4]. Several parameters govern the extraction in such a system [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The detailed general theory of the SLM extraction process with a stagnant acceptor has been thoroughly described by Jönsson et al [4]. Several parameters govern the extraction in such a system [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies have shown that the modification of the conditions worked-out in previous studies [18] enabled to determine the level of these amines in urine and tissue homogenates.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, Katarzyna and Casero applied the ion-pairing reagent bis-2-ethylhexylphosphate (BEHPA) to bind the polyamines for extraction, and the complex was broken under the acidic condition (0.1 mol/L HCl solution) for back-extraction [29,30]. Inspired by this, we present an analytical method to extract and determine polyamines and their N-acetylated metabolites from human urine in which the polyamines combine with the ion-pairing reagent in the aqueous phase and are extracted by PFSPE using polystyrene nanofibers as the sorbent.…”
Section: Introductionmentioning
confidence: 99%